Modern understanding of bacterial vaginosis - Aleksey A. Khryanin; German Yu. Knorring (IP Berlin A.V., 2021)
Bacterial vaginosis is an infectious non-inflammatory syndrome characterized by the replacement of the usual microflora by the polymicrobial associations of anaerobes and Gardnerella vaginalis. The review is devoted to current issues of this disease, including pathogenesis, clinical manifestations and approaches to laboratory diagnostics. Discussion issues of this disease related to the possibility of sexual transmission are discussed. Particular attention is paid to the factors causing the development of bacterial vaginosis. The classical concepts of diagnostic criteria for diagnosis are presented. Bacterial vaginosis is not characterized by the presence of a specific microorganism, but is the result of the formation of a bacterial biofilm on the epithelium of the vagina or foreskin. The main component of this biofilm is G. vaginalis. Bacterial vaginosis is caused by polymicrobial gardnerella biofilm, which can only be transferred as a whole (for example, with the help of key cells) only during sexual intercourse. Along with this, the authors discuss modern aspects related to the problem of microbial biofilm formation. In this regard, the authors propose to use a new term biofilm vaginosis, which more accurately reflects the essence of this problem. The modern possibilities of treating bacterial vaginosis are presented. The use of combined local therapy of nonspecific inflammatory processes of the vulvovaginal zone is becoming especially relevant at the present stage. The use of a local combination drug (Gainomax) with the widest possible spectrum of action allows doctors to achieve rapid relief of symptoms and high efficiency of therapy.